PENGGUNAAN MEDIA PAPAN KESADARAN LINGKUNGAN UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI BERSATU MENJAGA LINGKUNGAN RUMAH DAN SEKOLAH SISWA KELAS 2 SDN 02 MADIUN LOR - Wulansari, Devi; Fida Chasanatun; Yesi Novita Adisatriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem discussed in this research is low student scores, using environmental awareness board media to improve learning outcomes in united material to protect the home and school environment for class 2 students at SDN 02 Madiun Lor, Manguharjo District, Madiun City for the 2023/2024 school year, which is the background for the research this means that teachers do not use media in teaching, learning is still one way, where the teacher dominates learning so that students become passive in participating in learning. The data source for this research is class 2 students at SDN 02 Madiun Lor, Manguharjo District, Madiun City with a total of 12 students. This research was conducted with the aim of describing how to improve learning outcomes using unified material to protect the home and school environment of grade 2 students at SDN 02 Madiun Lor for the 2023/2024 academic year. This research was carried out in 2 cycles. Cycle 1 was carried out on March 2 2024 and Cycle 2 was carried out on May 8 2024. Student learning outcomes in. In cycle 1 only 7 students (58%) got the KKM score. In cycle 2 it increased to 12 students (100%). Research results are increasing. The conclusion of the research results is that improving learning using environmental awareness board media can improve the learning outcomes of class 2 students at SDN 02 Madiun Lor on the topic of uniting to protect the home and school environment.